2005
DOI: 10.1029/2004gl021782
|View full text |Cite
|
Sign up to set email alerts
|

X‐ray bursts associated with leader steps in cloud‐to‐ground lightning

Abstract: [1] X-ray and electric field measurements were made during five nearby negative natural lightning strikes in north central Florida during the summer of 2004. The observed X-ray emission typically was detected $1 ms before the first return stroke, during the stepped-leader phase, and had energies extending up to a few hundred keV. The X rays were produced in discrete, intense bursts emitted in coincidence with the formation of the leader steps, demonstrating unambiguously that the source of lightning X rays is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
229
1
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 181 publications
(250 citation statements)
references
References 17 publications
16
229
1
4
Order By: Relevance
“…Moore et al [2001] found x-rays during negative stepped leader descent at Langmuir Laboratory. Dwyer et al [2005] found similar results in Florida. Dwyer et al [2004aDwyer et al [ , 2004b have also detected X-radiation is association with rocket-triggered lightning at Camp Blanding, Florida.…”
Section: ]supporting
confidence: 62%
See 3 more Smart Citations
“…Moore et al [2001] found x-rays during negative stepped leader descent at Langmuir Laboratory. Dwyer et al [2005] found similar results in Florida. Dwyer et al [2004aDwyer et al [ , 2004b have also detected X-radiation is association with rocket-triggered lightning at Camp Blanding, Florida.…”
Section: ]supporting
confidence: 62%
“…These details are obviously important in understanding apparent discrepancies between findings by Schonland, Viljoen and Halliday, and the more recent results beneath thunderclouds [Moore et al, 2001;Dwyer et al, 2004aDwyer et al, , 2004bDwyer et al, , 2005.…”
Section: ]mentioning
confidence: 93%
See 2 more Smart Citations
“…Fig. 6(b) shows that the last two current pulses coincide with pronounced changes in the electric field at station 1, which are due to leader steps [25], [26].…”
Section: Currents Induced In the Vertical Conductor During Naturalmentioning
confidence: 96%